Bi-Directional Effect of Increasing Doses of Baclofen on Reinforcement Learning - Terrier, Jean; Ort, Andres; Yvon, Cédric; Saj, Arnaud; Vuilleumier, Patrik; Lüscher, Christian (Frontiers in Behavioral Neuroscience, 2011)
In rodents as well as in humans, efficient reinforcement learning depends on dopamine (DA) released from ventral tegmental area (VTA) neurons. It has been shown that in brain slices of mice, GABAB-receptor agonists at low concentrations increase the firing frequency of VTA-DA neurons, while high concentrations reduce the firing frequency. It remains however elusive whether baclofen can modulate reinforcement learning. Here, in a double blind study in 34 healthy human volunteers, we tested the effects of a low and a high concentration of oral baclofen in a gambling task associated with monetary reward. A low (20 mg) dose of baclofen increased the efficiency of reward-associated learning but had no effect on the avoidance of monetary loss. A high (50 mg) dose of baclofen on the other hand did not affect the learning curve. At the end of the task, subjects who received 20 mg baclofen p.o. were more accurate in choosing the symbol linked to the highest probability of earning money compared to the control group (89.55±1.39% vs 81.07±1.55%, p=0.002). Our results support a model where baclofen, at low concentrations, causes a disinhibition of DA neurons, increases DA levels and thus facilitates reinforcement learning.